SS 433: Flares and L 2 Overflow Spirals - Bowler, M (MDPI, 2024)
Flaring in the SS 433 microquasar is dominated by outbursts from material at distances from the centre of mass of the binary system comparable to the separation of the two components. This note completes a demonstration that ejected plasma leaves the system in the region of the L2 point, there overflowing the outer Roche lobe and giving rise to a spiral structure as it leaves the system as part of the local environment. It also provides a new measure of the mass ratio of the binary.